Human mitochondrial leucyl tRNA synthetase can suppress non cognate pathogenic mt‐tRNA mutations - Hue Tran Hornig‐Do; Arianna Montanari; Agata Rozanska; Helen A Tuppen; Abdulraheem A Almalki; Dyg P Abg‐Kamaludin; Laura Frontali; Silvia Francisci; Robert N Lightowlers; Zofia M Chrzanowska‐Lightowlers (EMBO Molecular Medicine, 2014)
Abstract Disorders of the mitochondrial genome cause a wide spectrum of disease, these present mainly as neurological and/or muscle related pathologies. Due to the intractability of the human mitochondrial genome there are currently no effective treatments for these disorders. The majority of the pathogenic mutations lie in the genes encoding mitochondrial tRNAs. Consequently, the biochemical deficiency is due to mitochondrial protein synthesis defects, which manifest as aberrant cellular respiration and ATP synthesis. It has previously been reported that overexpression of mitochondrial aminoacyl tRNA synthetases has been effective, in cell lines, at partially suppressing the defects resulting from mutations in their cognate mt‐tRNAs. We now show that leucyl tRNA synthetase is able to partially rescue defects caused by mutations in non‐cognate mt‐tRNAs. Further, a C terminal peptide alone can enter mitochondria and interact with the same spectrum of mt‐tRNAs as the entire synthetase, in intact cells. These data support the possibility that a small peptide could correct at least the biochemical defect associated with many mt‐tRNA mutations, inferring a novel therapy for these disorders.